ANTIBAKTERIAL ANALYSIS OF STARFISH Culcita novaeguineae EXTRACT IN THE WATER OF WEST BANYAK ISLAND ON BAKTERIA PATOGENIC Vibrio harveyiidanAeromonas hydrophila - Dewi, Shinta Rafida; Yoswaty, Dessy; F. Feliatra, F. Feliatra (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2019)
ABSTRACT Antibacterials are needed to treat diseases caused by pathogenic bacteria. One of the waters that can be used as a natural antibacterial compound is starfish. The aim of the study was to determine the antibacterial activity produced by starfish extract C. novaeguineae whether or not the effect of different concentrations of starfish extract on the inhibitory pathogenic bacteria V. harveyii and A. hydrophila. Synthesis of starfish extract was carried out with a concentration of 12.5%, 25 %, 50% and 100% In this study four repetitions were conducted on two test bacteria, positive control (Amoxicillin) and negative control (96% ethanol). The results showed that the antimicrobial content of C. novaeguineae extract could inhibit the growth of pathogenic bacteria with strong ability, the average value of the inhibition zone between 12.1 - 18.23 mm. After the One Way ANOVA test the hypothesis (H1) from this study was received, meaning that there were significant differences or there was an effect of the treatment of starfish extract concentration. Keyword:Extract C. novaeguineae, Zone Inhibit, Pathogenic Bacteria